Analysis of Fulfillment of Basic Needs of Post-Hospitalization Patients in Hospitals Based on Virginia Henderson's Theory - Alfid Tri Afandi; Prestasianita Putri; Nurfika Asmaningrum (STIKES Yayasan RS.Dr.Soetomo, 2026)
Post-hospitalization represents a critical transitional period in which patients must regain independence in fulfilling their basic needs. However, many experience persistent limitations after discharge due to inadequate education, lack of caregiver support, or reduced functional capacity. Guided by Virginia Henderson’s Nursing Need Theory, this study explored the fulfillment of basic needs among post-hospitalized patients and its associated factors. A cross-sectional study was conducted among 169 recently discharged adult patients from a public hospital in East Java, Indonesia. Data were collected using the Camberwell Assessment of Needs (CAN) , developed based on Henderson’s 14 fundamental needs. Independent variables included age, education, hospital length of stay, discharge education, and caregiver presence. Descriptive statistics, Chi-square tests, and multivariate logistic regression were used for data analysis. Approximately 37.9% of patients demonstrated high fulfillment of basic needs, while 25.4% had low fulfillment, particularly in hygiene, mobility, and rest domains. Logistic regression identified caregiver presence (AOR = 2.90, 95% CI = 1.70–4.95, p < 0.001) and discharge education (AOR = 2.40, 95% CI = 1.38–4.17, p = 0.002) as the strongest predictors of high need fulfillment. Higher education levels also increased likelihood (AOR = 1.60, p = 0.04), whereas age >50 years reduced it (AOR = 0.60, p = 0.03). The study confirms that discharge education and caregiver involvement significantly enhance post-hospitalization self-care independence. Nurses should integrate structured discharge teaching and caregiver training within transitional care models to ensure comprehensive fulfillment of patients’ basic needs, consistent with Henderson’s theory.Keywords: basic needs, post-hospitalization, Virginia Henderson theory, discharge education, caregiver support, nursing independence